Question and Answers Forum

All Questions      Topic List

Others Questions

Previous in All Question      Next in All Question      

Previous in Others      Next in Others      

Question Number 116965 by Dwaipayan Shikari last updated on 08/Oct/20

Σ_(k=1) ^∞ (−1)^(k+1)  ((sin(kθ))/(kθ))

k=1(1)k+1sin(kθ)kθ

Answered by Bird last updated on 08/Oct/20

let g(u) =Σ_(k=1) ^∞ (−1)^(k+1 ) ((sin(kx))/(kx))u^k  with ∣u∣<1  ⇒g^′ (u) =(1/x)Σ_(k=1) ^∞ (−1)^(k+1) sin(kx)u^(k−1)   =(1/x)Σ_(k=0) ^∞ (−1)^k sin((k+1)x)u^k   =(1/x)Im(Σ_(k=0) ^∞ (−1)^k  e^(i)k+1)x)  u^k )  but Σ_(k=0) ^∞ (−1)^k  e^(ix)  e^(ikx)  u^k   =e^(ix)  Σ_(k=0) ^∞ (−1)^k (u e^(ix) )^k   =e^(ix) ×(1/(1+ue^(ix) ))  =((cosx +isinx)/(1+ucosx +iu sinx))  =(((cosx+isinx)(1+ucosx−iu sinx))/((1+ucosx)^2  +u^2  sin^2 x))  =((cosx(1+ucosx)−iucosxsinx+isinx(1+ucosx)+usin^2 x)/(1+2ucosx +u^2 ))  ⇒Im(Σ...) =((sinx)/(u^2  +2u cosx +1))  ⇒g^′ (u) =((sinx)/(x(u^(2 )  +2u cosx +1)))  ⇒g(u) =((sinx)/x)∫  (du/(u^(2 ) +2u cosx +1))  but ∫  (du/(u^(2 ) +2u cosx+1))  =∫  (du/(u^2  +2u cosx +cos^2 x +sin^2 x))  =∫  (du/((u+cosx)^2  +sin^2 x))  =_(u+cosx =sinx z)    ∫  ((sinx dz)/(sin^2 x(1+z^2 )))  =(1/(sinx)) arctan(((u+cosx)/(sinx))) +C ⇒  g(u)=(1/x)arctan(((u+cosx)/(sinx))) +C  u=1 ⇒S(x) =(1/x)arctan(((1+cosx)/(sinx)))+C  =(1/x)arctan(((2cos^2 ((x/2)))/(2cos((x/2))sin((x/2)))))+C  =(1/x)arctsn((1/(tan((x/2))))) +C  =(1/x)((π/2) −(x/2)) +C  =(π/(2x))−(1/2) +C  x=π ⇒S(π)=0 =C ⇒  S(x) =((π−x)/(2x))

letg(u)=k=1(1)k+1sin(kx)kxukwithu∣<1g(u)=1xk=1(1)k+1sin(kx)uk1=1xk=0(1)ksin((k+1)x)uk=1xIm(k=0(1)kei)k+1)xuk)butk=0(1)keixeikxuk=eixk=0(1)k(ueix)k=eix×11+ueix=cosx+isinx1+ucosx+iusinx=(cosx+isinx)(1+ucosxiusinx)(1+ucosx)2+u2sin2x=cosx(1+ucosx)iucosxsinx+isinx(1+ucosx)+usin2x1+2ucosx+u2Im(Σ...)=sinxu2+2ucosx+1g(u)=sinxx(u2+2ucosx+1)g(u)=sinxxduu2+2ucosx+1butduu2+2ucosx+1=duu2+2ucosx+cos2x+sin2x=du(u+cosx)2+sin2x=u+cosx=sinxzsinxdzsin2x(1+z2)=1sinxarctan(u+cosxsinx)+Cg(u)=1xarctan(u+cosxsinx)+Cu=1S(x)=1xarctan(1+cosxsinx)+C=1xarctan(2cos2(x2)2cos(x2)sin(x2))+C=1xarctsn(1tan(x2))+C=1x(π2x2)+C=π2x12+Cx=πS(π)=0=CS(x)=πx2x

Commented by Dwaipayan Shikari last updated on 08/Oct/20

Thanking you

Thankingyou

Commented by Bird last updated on 08/Oct/20

you are welcome

youarewelcome

Terms of Service

Privacy Policy

Contact: info@tinkutara.com